Time‐dependent sorption of two novel fungicides in soils within a regulatory framework. Issue 12 (21st March 2016) - Gulkowska, Anna; Buerge, Ignaz J; Poiger, Thomas; Kasteel, Roy
Abstract: BACKGROUND: Convincing experimental evidence suggests increased sorption of pesticides on soil over time, which, so far, has not been considered in the regulatory assessment of leaching to groundwater. Recently, Beulke and van Beinum (2012) proposed a guidance on how to conduct, analyse and use time‐dependent sorption studies in pesticide registration. The applicability of the recommended experimental set‐up and fitting procedure was examined for two fungicides, penflufen and fluxapyroxad, in four soils during a 170 day incubation experiment. RESULTS: The apparent distribution coefficient increased by a factor of 2.5–4.5 for penflufen and by a factor of 2.5–2.8 for fluxapyroxad. The recommended two‐site, one‐rate sorption model adequately described measurements of total mass and liquid phase concentration in the calcium chloride suspension and the calculated apparent distribution coefficient, passing all prescribed quality criteria for model fit and parameter reliability. CONCLUSION: The guidance is technically mature regarding the experimental set‐up and parameterisation of the sorption model for the two moderately mobile and relatively persistent fungicides under investigation. These parameters can be used for transport modelling in soil, thereby recognising the existence of the experimentally observed, but in the regulatory leaching assessment of pesticides not yet routinely considered phenomenon of time‐dependent sorption. © 2016 Society of Chemical Industry